2013
DOI: 10.1111/jch.12212
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Nutraceutical Supplements for the Treatment of Hypertension: Part II

Abstract: Vascular biology, endothelial and vascular smooth muscle, and cardiac dysfunction play a primary role in the initiation and perpetuation of hypertension, cardiovascular disease, and target organ damage. Nutrient‐gene interactions and epigenetics are predominant factors in promoting beneficial or detrimental effects in cardiovascular health and hypertension. Macronutrients and micronutrients can prevent, control, and treat hypertension through numerous mechanisms related to vascular biology. Oxidative stress, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 75 publications
(370 reference statements)
0
28
0
1
Order By: Relevance
“…20 A vitamin D level of 60 ng/mL is recommended for optimal BP reduction and cardiovascular disease (CVD) risk reduction. [1][2][3][4] Vitamin B6 (Pyridoxine) Low serum vitamin B6 (pyridoxine) levels are associated with hypertension in humans. [1][2][3][4][24][25][26][27][28] High-dose vitamin B6 significantly lowered BP by 14/10 mmHg (P < 0.005) and serum catecholamine levels (P < 0.05) in a placebo-controlled study of 20 hypertensive subjects who were administered vitamin B6 at 5 mg/kg/day for four weeks.…”
Section: Vitamin Dmentioning
confidence: 99%
See 3 more Smart Citations
“…20 A vitamin D level of 60 ng/mL is recommended for optimal BP reduction and cardiovascular disease (CVD) risk reduction. [1][2][3][4] Vitamin B6 (Pyridoxine) Low serum vitamin B6 (pyridoxine) levels are associated with hypertension in humans. [1][2][3][4][24][25][26][27][28] High-dose vitamin B6 significantly lowered BP by 14/10 mmHg (P < 0.005) and serum catecholamine levels (P < 0.05) in a placebo-controlled study of 20 hypertensive subjects who were administered vitamin B6 at 5 mg/kg/day for four weeks.…”
Section: Vitamin Dmentioning
confidence: 99%
“…[1][2][3][4] Vitamin B6 (Pyridoxine) Low serum vitamin B6 (pyridoxine) levels are associated with hypertension in humans. [1][2][3][4][24][25][26][27][28] High-dose vitamin B6 significantly lowered BP by 14/10 mmHg (P < 0.005) and serum catecholamine levels (P < 0.05) in a placebo-controlled study of 20 hypertensive subjects who were administered vitamin B6 at 5 mg/kg/day for four weeks. 25 In a placebo-controlled trial over 12 weeks, in which participants were given 800 mg lipoic acid and 80 mg pyridoxine, results showed that serum lipoic acid and pyridoxine, urinary albumin, serum malondialdehyde, and SBP decreased significantly in the supplement group compared to the placebo group (P < 0.05).…”
Section: Vitamin Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Störungen im Elektrolythaushalt sind bei Patienten mit Hypertonie gut dokumentiert [2][3][4]. Antihypertensive Medikamente selbst spielen bei der Entstehung von Mineralstoffmängeln eine Rolle [5].…”
Section: Elektrolyte Und Hypertonieunclassified